Family as a source of moral education - Kłos-Skrzypczak, Aleksandra (Śląskie Studia Historyczno-Teologiczne, 2022)
It seems that modern society does not need to be convinced of the need to educate young generations, especially the need for moral education. Observing the customs that are made more specific in social and family life, one can notice its serious deficit. The dignity of human life is not only a social-moral value, but should be the basis of every educational process. This article says that it is up to parents to raise the young generation toward values. The text deals with the subject of the dignity of human life, because the concern for young citizens should begin in the prenatal period, which confirms the position of the Catholic Church. Author presents argument that the family is the basic place of raising children. In conclusion, the text says directly to what values the young generation should be brought up.